1987
DOI: 10.1016/s0735-1097(87)80215-2
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular pacing reduces the rate of left ventricular relaxation and filling

Abstract: Right ventricular pacing alters left ventricular synchrony and loading conditions, each of which may independently influence left ventricular relaxation. Addition of a properly timed atrial contraction by using sequential atrioventricular (AV) pacing minimizes changes in left ventricular loading conditions, but ventricular asynchrony persists. To separate the effects of altered loading from those of asynchrony, the effects of right ventricular pacing and sequential AV pacing on the rate of isovolumic pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(80 citation statements)
references
References 21 publications
7
69
0
4
Order By: Relevance
“…On the basis of TDI cross-correlation analysis, it has been claimed that apical pacing produces systolic dyssynchrony with preserved diastolic synchrony 20 . However, in agreement with previous studies 13,21 , our experience indicates that a significant diastolic impairment acutely results from ventricular pacing, affecting both the isometric relaxation and the filling process. Indeed, LVP min and E-wave DT were increased, and E' was reduced.…”
Section: Left Ventricular Haemodynamicssupporting
confidence: 93%
“…On the basis of TDI cross-correlation analysis, it has been claimed that apical pacing produces systolic dyssynchrony with preserved diastolic synchrony 20 . However, in agreement with previous studies 13,21 , our experience indicates that a significant diastolic impairment acutely results from ventricular pacing, affecting both the isometric relaxation and the filling process. Indeed, LVP min and E-wave DT were increased, and E' was reduced.…”
Section: Left Ventricular Haemodynamicssupporting
confidence: 93%
“…Myocardial relaxation is influenced by chamber load and homogeneity of activation. [15][16][17][18] In previous work, we did not find an improvement in ventricular relaxation with resynchronization therapy, 4 and Auricchio et al 5 found that CRT had only a modest effect on relaxation. This may, however, reflect the more complex influence of Figure 3.…”
Section: Discussionmentioning
confidence: 67%
“…Se ha demostrado que el retraso electromecánico intraventricular, los tiempos de contracción y relajación y la magnitud de la desincronización de la pared ventricular no son idénticos entre las dos situaciones 23 . Sin embargo, no es menos cierto que la estimulación cró-nica desde ápex de VD se asocia a efectos hemodiná-micos adversos [24][25][26] . Además, estudios clínicos y experimentales han demostrado cambios histopatológicos que podrían provocar a largo plazo un remodelado ventricular [27][28][29][30] .…”
Section: Discussionunclassified